THE INFLUENCE OF CULTURAL CONTACTS ON THE SOCIAL STRUCTURE OF THE TURAN CIVILIZATION POPULATION (Scientific journal of the Fergana State University, 2026)
A natural question arises: how were lapis lazuli, chlorite, and other minerals produced and processed, and how were trade relations conducted? In our opinion, to answer this question, it is first necessary to abandon outdated views of the regions east of Mesopotamia – namely Iran and Central Asia – as “peripheral” areas. At the same time, there is a need to consider the scholarly perspective that these regions did not develop in isolation, without cultural and economic connections.